Performance and efficiency of joints in precast members - Subramanian, K.; Gopinathan, M.J. (Journal of Structural Engineering, 2024)
The usage of precast concrete began about 70 years ago. But the technology has maintained its status in the construction industry as “The Least Understood form of Construction”. The advantages of the pre-cast construction are not explored by most part of the world especially by the developing countries. This paper presents the results of three portal frames subjected to lateral loading in which two specimens are precast frames and one is control specimen. The results are compared with control specimen. The effi ciency and performance of beam-column joints and beam-beam joints are studied with respect to control specimen. The ultimate load of precast specimen is 80 percentage of control specimen and load deflection curves as well as first cracking loads are compared.